1988
DOI: 10.1038/bjc.1988.156
|View full text |Cite
|
Sign up to set email alerts
|

Structural damage to lymphocyte nuclei by H2O2 or gamma irradiation is dependent on the mechanism of OH. radical production

Abstract: Summary Normal human lymphocytes were exposed to OH radicals produced indirectly by exposure to H202 or directly by gamma irradiation. Using a flow cytometry technique to measure changes in nucleoid size, it was found that generation of OH in each system produced a characteristic relaxation in nuclear supercoiling. Exposure of cells to H202 produced a metal-dependent step-wise relaxation in extracted nucleoids, while gamma irradiation induced a gradual dose-dependent increase in nucleoid size. The sitespecific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Furthermore, a significant decrease in the activity of GPx was observed in SLE and RA patients which are similar to the study of Turgay et al (2007) in SLE andOzturk et al (1999) in RA patients. The hydrogen peroxide is a lipophilic ROS that permeates lipid membranes and is capable of damaging DNA (Allan et al 1988). It has been suggested that the reduced activities of CAT and GPx in SLE and RA patients could be due to the inactivation of the enzymes by over production of H 2 O 2 (Ortona et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, a significant decrease in the activity of GPx was observed in SLE and RA patients which are similar to the study of Turgay et al (2007) in SLE andOzturk et al (1999) in RA patients. The hydrogen peroxide is a lipophilic ROS that permeates lipid membranes and is capable of damaging DNA (Allan et al 1988). It has been suggested that the reduced activities of CAT and GPx in SLE and RA patients could be due to the inactivation of the enzymes by over production of H 2 O 2 (Ortona et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Ultraviolet (UV) irradiation [18,19] and hydrogen peroxide [20,21] are well-studied DNA damaging agents that effectively introduce single-and double-strand breaks in chromosomal DNA in vivo as well as in vitro. We examined the nuclease digestion pattern in cells pre-exposed to UV light (at 312 nm) for 15 min at 4°C before chloroquine treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, antigenic and mutagenic changes may occur which could become incorporated into the germline genes. ROS must permeate both cellular and nuclear membranes in order to gain access to organelle-bound DNA; hydrogen peroxide is sufficiently lipophilic to do this [4].…”
Section: Introductionmentioning
confidence: 99%
“…Human IgG, when exposed to ROS, becomes antigenic and produces characteristic autofluorescence [2,3]. Similarly, reactivity of ROS towards DNA induces conformational change [4], base damage [5], both single-and double-strand breaks and often the subsequent production of clastogenic factors [8]. In addition, antigenic and mutagenic changes may occur which could become incorporated into the germline genes.…”
Section: Introductionmentioning
confidence: 99%